Evaluation of Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) Parameters for Establishing A Mass Rearing on Ceratitis Capitata (Wied.) (Diptera: Tephritidae) - yahia rahal; Ahmed Mazih; Rachid Elaini (Andalasian International Journal of Entomology, 2025)
The Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) is one of the major fruit crop pests in Morocco and the world. The braconid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) is a larval-pupal endoparasitoid that can be used as a native biological control agent against this pest. In this study, several rearing parameters were controlled to optimize a profitable rearing strategy. density and quality of host larvae, 2) exposure time to parasitoids, and 3) sex ratio of parasitoids. To investigate the effect of each parameter, we concluded that the third instar of C. capitata in a proportion of 2:1 larva: female, exposed for 24h to parasitoids with a proportion of 1:1 and 2:1 female: male. These parameters demonstrate good performance, influenced by parasitism at approximately 80%, high flight ability at 88%, low pupal mortality, and high female progeny production. A diet of pure honey and water for parasitoid adults gives a high longevity of almost 70 days. Other parameters did not differ much throughout the trials. The results in our study can be used to provide a suitable protocol and environment for mass rearing of D. longicaudata as a biological control against C. capitata.